Integrating signaling pathways to pattern cells of the fin fold - Ho, Charmaine Min (Nanyang Technological University, 2021)
During zebrafish median fin fold (MFF) development, mesoderm-derived mesenchymal fibroblasts migrate outwards into the fin fold, towards the Apical Ectodermal Ridge (AER). The Platelet Derived Growth Factor (PDGF) and Bone Morphogenetic Protein (BMP) are small diffusible ligands expressed in the AER, with their corresponding receptors expressed in the fin mesenchyme, and are suspected to influence this migration process. However, little is known about their roles in the zebrafish MFF. In this study, the function of PDGF and BMP signaling in zebrafish fin fold mesenchymal fibroblast migration was investigated using the chemical inhibitors PDGFR Tyrosine Kinase Inhibitor V and K02288 respectively. Transgenic lines Tg(-1.5hsp70l:smurf1-P2A-mCherry-CAAX,crybb:ECFP) and Tg(-1.5hsp70l:bmpr2bSF-P2A-mCherry-CAAX,crybb:ECFP) were also generated for the selective downregulation of canonical and LIMK1-mediated non-canonical BMP signaling respectively. PDGF signaling inhibition resulted in a supposed migration defect, reduction in fin fold mesenchymal fibroblast numbers, and increase in acridine orange-positive apoptotic cells within the fin mesoderm. BMP signaling inhibition resulted in a migration defect with a fall in fibroblast branching and cell area and an increase in cell aspect ratio. Taken together, our findings suggest a possible role for PDGF in the survival and/or migration of mesenchymal fibroblasts, and for BMP in mesenchymal fibroblast morphology and migration.